Towards robust predictive fault-tolerant control for a battery assembly system - Seybold, Lothar; Witczak, Marcin; Majdzik, Paweł; Stetter, Ralf (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the modeling and fault-tolerant control of a real battery assembly system which is under implementation at the RAFI GmbH company (one of the leading electronic manufacturing service providers in Germany). To model and control the battery assembly system, a unified max-plus algebra and model predictive control framework is introduced.
Keywords: max-plus algebra; interval analysis; battery assembly; model predictive control; fault-tolerant control